EXPERIMENTAL RESEARCH OF THE SYSTEM 0,425C3H8 + 0,575He - 0,426N2O + 0,574СН4 - Moldabekova, M.S.; Poyarkov, I.V.; Asembaeva, M.K.; Beketaeva, M.T. (Recent Contributions to Physics, 2017)
The mixing process in the gravitational stable four component gas system where two components have equal diffusive properties is studied by the two flasks method. It is shown experimentally that in dependence on pressure two regimes of mixing notably diffusive and convective are observed. The convective flow having the constant intensity is directed from the upper flask of apparatus into the lower one.